Electric drive training kit sebagai produk inovasi media pembelajaran praktikum mahasiswa pendidikan vokasi: Analisis uji praktikalitas - Doni Tri Putra Yanto; Oriza Candra; Citra Dewi; Hastuti Hastuti; Hermi Zaswita (JINoP (Jurnal Inovasi Pembelajaran), 2022)
This study discusses the practicality test analysis of an innovative product of practicum learning media, namely the Electric drive training kit which is used in electric drive practice lesson for vocational education students, Industrial Electrical Engineering study program. This development is carried out because of the unavailability of practicum learning media that are in accordance with the characteristics of the material and oriented to industrial developments which resulted in the learning process being not optimal. The purpose of the study is to reveal the practicality level of using the Electric drive training kit as a practicum learning media by users, namely lecturers and students. The practicality level is analyzed based on data from lecturers' assessments and student assessments after using the product in the learning process through filling out the practicality assessment sheet. The data are analyzed using percentage analysis and interpreted using a practical interpretation table. Practicality assessment sheets with a Likert scale are used as data collection instruments. The results show that based on the responses of lecturers and students, this media was very practical to use as a practicum learning media in the  electric drive practice lesson. Thus, it can be concluded that the Electric drive training kit is very practical to use as a learning media to support the implementation of learning to be more optimal.